La commercialisation de Dacryodes edulis dans la zone forestière humide du Cameroun - Awono, A.; Ndoye, O.; Schreckenberg, Kate (Presses Universitaires d'Afrique, 2002)
This paper sheds light on the marketing of Dacryodes edulis in the humid forest zone of Cameroon. The results of the study show that the marketing margins are related to the type of fruits, its state (quality), the selling place and the market supply, which also depend on the production period. The value of Dacryodes sold in 1999 in 9 markets in the humid forest zone of Cameroon is 1049 million CFA Francs for a volume of 2324 tons. In some of the markets, the weekly marketing margins obtained by traders is more than two times greater than the SMIG (minimum wage) that prevails in Cameroon. The results also show that farmers receive 75 percent of the price paid by consumers. This percentage should not make us believe that farmers cannot get more from the production and marketing of Dacryodes edulis. For this to happen, it is imperative that farmers organise themselves into producer groups, which will allow them not only to get access into the market in a less costly way, using economies of scale but also to gather strategic information, which could permit them identify more profitable markets.